Pendekatan Hermeneutika Filosofis Untuk Memahami Makna Profesi Guru Agama Dalam Dinamika Tuntutan Mutu Global - Jamil, Sabarun; Aimah, Siti (JURNAL MANAJEMEN PENDIDIKAN, 2026)
A PHILOSOPHICAL HERMENEUTIC APPROACH TO UNDERSTANDING THE MEANING OF THE RELIGIOUS TEACHER PROFESSION IN THE DYNAMICS OF GLOBAL QUALITY DEMANDSThis research is based on the reality of the changing meaning of the profession of religious teachers amidst the increasingly complex dynamics of global demands for quality education. The purpose of this research is to deeply understand the meaning of the profession of religious teachers using a philosophical hermeneutic approach, particularly in responding to the tension between the demands of global quality that are technocratic in nature and transcendental religious values. This research uses a qualitative interpretative method with the research location at MTs Darul Ulum Tirta Kencana Unit 6. Data collection techniques were carried out through in-depth semi-structured interviews, participant observation, and documentation studies with religious teachers, madrasah principals, deputy heads of curriculum, and students as supporting informants. Data analysis was carried out hermeneutically by following the principle of the hermeneutic circle, namely a continuous dialogue between empirical data, subjective experiences of informants, and the surrounding socio-historical context, accompanied by data reduction, data presentation, and drawing conclusions. The results of the study indicate that the meaning of the profession of religious teachers has shifted from a normative role to a reflective-contextual role, influenced by the historical experiences of teachers and the social context of the madrasah. Furthermore, the professionalism of religious teachers is understood holistically as an integration of pedagogical competence and morality. This research confirms that global quality demands can provide a reflective space to enrich the meaning of the religious teaching profession in a humanistic, contextual way, and oriented toward developing student character without losing its spiritual values.